Physiology, behaviour and inter-species interactions of jellyfish under changing ocean conditions - Boco, Sheldon Rey (Griffith University, 2021)
Marine stressors can cause negative impacts on physiology, behaviour, morphology, reproduction and survival of many invertebrate species. Key stressors include the concurrent rise of sea surface temperatures and lowering of pH, under the processes of ocean acidification (OA) and decreasing oxygen availability in the ocean. Changes to these fundamental variables in marine ecosystems may harm invertebrate populations and, in turn, threaten overall biodiversity. Jellyfish are a conspicuous component of marine ecosystems that provide numerous ecosystem services, and it is unclear how changing ocean conditions may affect their survival, physiology, and behaviour. To address this uncertainty, this thesis explores the effects of changing ocean conditions on a suite of biological and ecological responses of jellyfish. A series of experiments was performed to explore how changes in pH, dissolved oxygen (O2) and temperature might influence the behaviour, physiology, metabolism, and inter-species interactions involving jellyfish. The studies here may help elucidate the future proliferation and performance of jellyfish in response to anthropogenic marine stressors. This thesis tested three hypotheses: 1) That ocean warming and acidification will alter the behaviour, respiration rate and metabolite composition of jellyfish polyps (Chapter 2), 2) that coastal deoxygenation and elevated pCO2 will reduce settlement success and movement behaviour of jellyfish creeping polyps (Chapter 3), and 3) that elevated pCO2 will impair detection of jellyfish medusa by phyllosoma larvae of lobsters (Chapter 4). The individual and combined effects of ocean warming and acidification on behaviour, survival, asexual reproduction, respiration, and metabolic composition of polyps of Carukia barnesi were examined in Chapter 2. My results demonstrate that polyps of C. barnesi can survive and reproduce under even the most extreme climate scenario predictions (lowest pH and elevated temperature) and several sublethal responses that might influence their overall fitness were detected. Sublethal effects included reduced asexual reproduction, increased respiration rates, reduced mobility and suppression of various endogenous metabolites in extreme conditions. For the most part, effects were observed to occur in response to the stressors individually (i.e., pH and temperature) but not in combination, thus failing to support the hypotheses that greater sublethal effects would manifest when polyps were exposed to combined stressors. Moderate pH also had minimal effect, highlighting the importance of testing moderate climate scenarios which are more likely to occur than predictions of extreme scenarios. These findings suggest that Irukandji polyps will likely survive in moderate and extreme climate conditions projected to occur by the year 2100, but that rates of asexual reproduction may be slower if temperatures warm by 2 °C and/or pH declines to ~7.7 or lower. Coastal deoxygenation (CD) and coastal acidification (CA) co-occur in many ecosystems because nutrient enrichment provides excess organic matter that intensifies aerobic respiration associated with decomposition, thereby depleting O2, increasing CO2 and lowering pH. I therefore tested the individual and combined effects of CD and CA on the survival, number of tentacles, settlement success and movement behaviour of creeping polyps of the Irukandji jellyfish A. alata in Chapter 3. I found that CD increased survival rates, CD and CA in combination did not impair movement behaviour, and that both stressors independently increased rates of settlement. These findings suggest that more creeping polyps of A. alata may settle in low pH and hypoxic conditions typical of those occurring in eutrophic tropical reef ecosystems. Evidence suggest that OA can affect symbiosis and prey recognition through disruption of sensory or nervous system functions. In Chapter 4, I tested whether OA impairs the survival and detection of jellyfish by predatory phyllosoma larvae of the lobster Thenus australiensis, and whether this in turn is related to changes in biochemical profiles of the lobster. Results show that extreme OA is detrimental to the survival and ability of lobster phyllosomas to interact with jellyfish. The phyllosomas had lower survival and moulting rates, spent more time away from jellyfish, and exhibited reduced respiration rates under extreme OA. The majority of water soluble (polar) metabolites were suppressed in moderate and extreme pH conditions. Phyllosomas will likely compensate for metabolic costs to thrive in future moderate OA conditions that will likely occur in marine ecosystems. If extreme OA were to occur, these results suggest that this may contribute to a reduction in the population of larval lobsters. Overall, this study contributes to understanding of underexamined potential effects of OA on interactions between jellyfish and invertebrate symbionts. In testing the various hypotheses, an overarching goal of my thesis was to use environmentally relevant simulations and novel analytical approaches to improve our understanding of sublethal responses and interactions involving jellyfish in response to coastal and global anthropogenic stressors associated with climate change. My findings disagree with many prior studies that have suggested that climate change and OA may benefit jellyfish. The findings here show that effects of anthropogenic stressors are inconsistent across jellyfish taxa since other species do not exhibit impaired eco-physiological responses under similar stressors. Responses of single species and inter-species interactions to anthropogenic stressors may influence population success of jellyfish under increasing magnitude of oceanic and coastal stressors.